Banking on Deposits: Maturity Transformation without Interest Rate Risk - DRECHSLER, ITAMAR; SAVOV, ALEXI; SCHNABL, PHILIPP (The Journal of finance (New York), 2021)
We show that maturity transformation does not expose banks to interest rate risk—it hedges it. The reason is the deposit franchise, which allows banks to pay deposit rates that are low and insensitive to market interest rates. Hedging the deposit franchise requires banks to earn income that is also insensitive, that is, to lend long term at fixed rates. As predicted by this theory, we show that banks closely match the interest rate sensitivities of their interest income and expense, and that this insulates their equity from interest rate shocks. Our results explain why banks supply long-term credit.